Characterisation of ERK distribution and activity in rat pheochromocytoma cells : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Molecular Biology at Massey University - MacCormick, Matthew Edgar (Massey University, 1998)
Nerve growth factor (NGF) binds to the NGF receptor, TrkA, at the tips of nerve cell axons, sending a signal that prevents programmed cell death and causes survival, growth, and differentiation of the nerve cell. Both NGF and TrkA have been demonstrated to be retrogradely transported from axon tips to nerve cell bodies, however the mechanism of this transport, and its function, is strongly debated. Using a recently developed cell fractionation protocol in conjunction with in vitro reactions using an ATP regenerating system, our lab has isolated small vesicles containing NGF bound to activated TrkA. These vesicles may provide a vehicle for retrograde transport of the NGF signal and initiation of signal transduction in the cell body. ERK1 is a serine/threonine kinase that is activated by NGF-activated TrkA. Prolonged ERK1 activity is characteristic of cells stimulated by NGF. The purpose of the experiments in this thesis was to characterise the intracellular distribution and activity of ERK1 before and after NGF stimulation, in rat pheochromocytoma (PC12) cells, which are a good model for nerve cells. We have found that ERK1 activity is redistributed between cell compartments after NGF stimulation of PC12 cells. ERK1 activity increased in sedimentable fractions that emerged from mechanically permeabilised cells after NGF treatment and in vitro reactions with ATP. Importantly, the results from glycerol velocity gradient experiments showed that ERK1 was not associated with membranes. Instead ERK1 was found in a rapidly sedimenting particle whose sedimentation was not affected by detergent solubilisation. These results suggest that ERK1 is recruited into a protein complex, after activation, which may be an important step in signal transduction. Formation of this complex is likely to be downstream of signalling vesicles containing NGF bound TrkA.
Keywords: Protein kinases; Nerve growth factor; Neurons -- Growth; Pheochromocytoma